ANALISIS ‘INDEXES’ (BENEISH RATIO INDEX) UNTUK MENDETEKSI KECURANGAN LAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI PER DESEMBER 2014 - 2015 - Harahap, Ilham Akbar; Desmiyawat, Desmiyawat; Julita, Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted to determine percentage manufacturing companies listed on IDX at 2014-2015 that included manipulator, non manipulator, grey area, manipulator parameter index entry in the index count Days Sales in Receivables Index (DSRI),Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index(SGI), Depreciation Index (DEPI), Sales General and Administrative Expenses Index (SGAI), Leverage Index (LVGI) dan Total Accruals to Total Assets Index (TATA). The method of collecting data was documentation. The population were 144 manufacturing companies on IDX. Analysis of data using Beneish Ratio Index. The results of this research shows that the manufacturing company listed on the Indonesia Stock Exchange (BEI) 2014- 2015 were classified manipulator 19,04%, non manipulator 54,76%, grey area26,19%, exceed the parameter index DSRI 4.76%, exceed the parameter index GMI 4,76%, exceed the parameter index AQI 30,95%, exceed the parameter index SGI 4,76%, exceed the parameter index DEPI 14,2%. exceed the parameter index SGAI 45,23%. exceed the parameter index LVGI 23,80%. exceed the parameter index TATA 11,90%.Keywords :Fraud, Financial Statement, Financial Statement Fraud, Fraud Early Detection of Financial Statement